How to Promote Personal Financial Education - Findings from Finnish University Students’ Financial Literacy Study - Mandmaa, Sirli (International Journal of Educational Technology and Learning, 2021)
The results of The Organization for Economic Co-operation and Development (OECD) and several studies show that the current level of financial literacy of the population can guarantee sustainability neither for them nor for society. As the financial crises and the situation during the COVID-19 pandemic have demonstrated, people have difficulty coping even with short-term income losses. This highlights the need to raise the level of financial literacy, which requires promotion of personal financial education, and specifically, –results from research. This paper presents the results from the first financial literacy survey in Finland that was organized among higher education students. The aim of the study was to assess the financial literacy and compare the results with similar studies to identify bottlenecks that could be improved through the promotion of financial education. The results of the survey showed a good level of students' financial knowledge, but also pointed out topics where the level of knowledge was low - areas like insurance and interest rate changes. The results indicated that financial literacy scores of students in mathematics-based academic disciplines are significantly better than those of students in non-numerical disciplines. A positive link was found between long-term planning and higher levels of financial literacy.